Patients with unilateral anterior knee pain present bilateral deficits in quadriceps neuromuscular function and hip joint flexibility: A cross-sectional study - Kim, S.; Park, S. (Journal of Athletic Training, 2019)
Context: Unilateral anterior knee pain (AKP) may cause bilateral quadriceps weakness and inhibition. However, it is unclear how unilateral AKP affects bilateral quadriceps endurance and hip joint flexibility. We examined if patients with unilateral AKP present bilateral deficits in quadriceps neuromuscular function and hip joint flexibility when comparing with the matched healthy knees. Methods: Study design: Cross-sectional study. Setting: Laboratory. Patient population: Twenty-three patients with unilateral AKP (8 females,15 males; age: 22.0 ± 1.2 years, height: 171.7 ± 2.9 cm, mass: 70.6 ± 7.5 kg, body mass index: 23.8 ± 1.9 kg/m2, time since pain: 46.5 ± 15.0 months) and 23 matched healthy controls (8 females, 15 males; age: 22.7 ± 1.3 years, height: 171.0 ± 3.0 cm, mass: 70.8 ± 5.6 kg, body mass index: 24.1 ± 1.5 kg/m2). Outcome measures: Pain perception using visual analog scale (cm), functional outcomes using the Lower Extremity Functional Scale (score), and knee joint effusion (sum of the circumferences of the superior and inferior pole of patella in cm) were obtained. Quadriceps neuromuscular function was assessed by strength (isometric in N·m/kg), endurance (isokinetic at 180°/s in N·m/kg), and voluntary activation (central activation ratio). Hip joint flexibility was measured by single straight leg raise and modified Thomas test (°). Statistical analyses: Parametric or a non-parametric tests (P < .05) with calculations of Cohen's d effect size with 95% confidence intervals were performed. Results: Knee joint circumference was not different, indicating that our AKP patients did not have joint effusion (P = .28). As compared with the matched healthy controls, patients with unilaterall AKP showed (1) a greater pain perception (0.0 ± 0.0 versus 4.3 ± 0.7 cm, P < .0001, d = 3.50); (2) a lower score on functional outcomes (79.6 ± 0.3 versus 56.3 ± 4.6 score, P < .0001, d = 1.20); and (3) a less quadriceps strength (3.5 ± 0.2 versus 2.8 ± 0.2 N·m/kg, P < .0001, d = 1.15), endurance (peak torque: 1.65 ± 0.07 versus 1.51 ± 0.05 N·m/kg, P = .02, d = 0.65; total work: 76.5 ± 3.0 versus 69.6 ± 2.3 N·m/kg, P = .01, d = 0.75), and voluntary activation (0.95 ± 0.02 versus 0.83 ± 0.03, P < .0001, d = 1.41), and hip joint flexibility (flexion: 86.7 ± 4.6 versus 72.5 ± 4.3°, P = .001, d = 0.92; extension: 11.9 ± 1.4 versus 7.8 ± 2.3°, P = .03, d = 0.64). Conclusions: Our data suggest that unilateral AKP, without the absence of joint effusion, results in bilateral deficits in quadriceps neuromuscular function and hip joint flexibility. Since chronic AKP may cause bilateral symptoms, clinicians should consider restoration of both neuromuscular function and the joint flexibility along with pain reduction.